The Judge's Judgment with his Personal Knowledge between the Permission and Prohibition - a Comparative Study - Yahiaoui, Laala (Journal of Legal Studies and Researches, 2023)
The paper is about the judge's ruling with his personal knowledge, about which the jurists were divided into two opinions: an opinion that absolutely permits it, and an opinion that completely denies it. In addition, each of them has its evidence and arguments from the Quran, the Sunnah, and the opinion of statutory laws and modern legislation.